2. Some Aspects of Developing Musical Thinking in the Training of Musical Student - Tetelea Margarita; Glebov Ana (Sciendo, 2016)
This article examines various approaches and methods used to develop musical thinking in students. It also reveals some of the principles, developed by a number of scientists to facilitate the process. One of the new principles of developing musical thinking is internalization of music, proposed by the Moldovan professor and musicologist Ion Gagim, who in his works justifies its use from the philosophical, musicological, psychological and pedagogical perspectives.